Household debt and household spending behavior: evidence from Malaysia (hutang isi rumah dan tingkah laku perbelanjaan isi rumah: Bukti dari Malaysia) - Cai, Yunchao; Abdullah Yusof, Selamah; Mohd Amin, Ruzita; Mohd Arshad, Mohd Nahar (Universiti Kebangsaan Malaysia, 2020)
Using data collected from urban households in the Klang Valley, Malaysia, this study examined the impact of household debt on urban household consumption decisions. The findings revealed that household debt does not generally affect consumption decisions, except in the case of expenditure on vacation, which tends to be reduced for households facing high levels of debt. Furthermore, general financial wellness tends to be the main factor affecting consumption rather than debt. Households with poorer financial wellness make more frequent cuts to daily meals, fruit, utility, transportation, clothing, medical care, vacations, and leisure activities. Although the impact of debt on consumption is not extensive, it must be closely monitored to ensure that the risk is contained and that the wellbeing of households is not adversely affected.